DEVELOPMENT OF PLAYING EDUCATION FOOTBALL MULTIMEDIA TO IMPROVE LEARNING OUTCOMES IN FOOTBALL THEORY AND PRACTICE - I Made Satyawan; I Wayan Lasmawan; I Wayan Artanayasa; Ketut Chandra Adinata Kusuma; I Dewa Made Aryananda Wijaya Kusuma; Yovhandra Ockta (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The limited availability of multimedia resources in football science, coupled with a lack of innovation and updates in the learning materials, significantly impacts student motivation and learning outcomes. Furthermore, there are several factors influencing learning results, such as learning motivation, student comprehension, available learning facilities, and the media employed by lecturers during teaching. One of the strategies to be implemented in learning is the use of interactive multimedia in the Football Practice Theory course to boost student motivation and improve learning outcomes. The aim of this research is to develop football multimedia for Physical Education (PE) in the context of Football Practice Theory. This study also examines the feedback from both lecturers and students regarding the development of PE football multimedia in Football Practice Theory. The research follows a Research & Development (R&D) approach, utilizing the ADDIE development model, which includes the following steps: A for Analysis, D for Design, D for Development, I for Implementation, and E for Evaluation. The validity tests conducted by content experts, as well as media and design experts, resulted in an average score of 1.00, categorizing it as very good. The effectiveness of the multimedia, based on the N-Gain calculation, was 0.78, indicating its effectiveness. The N-Gain value was derived from the difference in average pre-test and post-test scores. Student feedback resulted in an average score of 67.5, categorized as very valid, while lecturer feedback yielded an average score of 47, also categorized as very valid. Based on all the evaluations conducted on the PE football multimedia in Football Practice Theory, the developed multimedia is deemed appropriate as a learning resource for enhancing student motivation and learning outcomes.